La higiene en el ámbito educativo - Marcillo López, Marco Vinicio (2017)
This study constitutes a response to a problem of health deficiency in the personal presentation of students of Basic General Education Irak Republic School; whose effects have high rates of impact on academic performance and interpersonal relationships. The main objective of this research is to determine the degree of incidence of personal hygiene habits and the application of rules and cleanliness rules in the academic performance of students. The research has a quantitative approach, due to its characteristics is descriptive, while it corresponds to the bibliographic - documentary and field modalities. For data collection, the techniques: interview and the survey were applied, through the use of instruments such as the question guide and the questionnaire respectively. The results obtained in this process reveal the shortcomings of management, teaching and the parents neglect in the students’ personal health. Therefore, the significant contribution of the project constitutes the institutional diagnosis of the study problem that broadly shows a vast sector of students with personal hygiene shortcomings in their body and dressing that has a negative impact on school performance.